Disc brake pads

By non-uniform scorching on the friction surface of the friction material of the disc brake lining block, the problems of thermal fading and insufficient braking performance in the early stages of use are solved, and effective thermal fading prevention and braking performance improvement are achieved.

CN114555969BActive Publication Date: 2024-12-13NISSHINBO BRAKE INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080069777.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-03
Filing Date
2020-09-28
Publication Date
2024-12-13
Estimated Expiration
2040-09-28

AI Technical Summary

Technical Problem

The existing disc brake lining blocks are prone to heat fading in the early stages of use, resulting in a reduction in braking efficiency and the inability to obtain sufficient braking efficiency.

Method used

By performing non-uniform scorching on the friction surface of the friction material, a mixture of parts with large heat history and relatively small parts of the scorching treatment are formed, and a part of organic matter such as cashew shell oil friction powder is removed, thereby on the friction surface Form a coating to improve braking efficiency.

Benefits of technology

It effectively prevents the heat fading phenomenon of the disc brake lining block in the early stages of use, and at the same time obtains good and stable braking performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114555969B_ABST
    Figure CN114555969B_ABST
Patent Text Reader

Abstract

[Problem] The present invention provides a disc brake pad with a friction material, the friction material having a friction surface that has been subjected to a scorching treatment, which can prevent the disc brake pad from thermal decay in the initial use and obtain sufficient braking performance. [Solution] In a disc brake pad with a friction material, the friction material has a friction surface that has undergone a thermal history through a scorching treatment, and there are a mixture of parts with a large thermal history of the scorching treatment and parts with a relatively small thermal history on the friction surface. When the mass reduction rate of the friction material that has not undergone a thermal history of the scorching treatment when subjected to a 500°C thermogravimetric analysis is A, the mass reduction rate of the part with the largest thermal history of the scorching treatment on the friction surface when subjected to a 500°C thermogravimetric analysis is B1, and the mass reduction rate of the part with a relatively small thermal history of the scorching treatment relative to the part with the largest thermal history of the scorching treatment on the friction surface when subjected to a 500°C thermogravimetric analysis is B2, the following formula is satisfied. Formula: 30≤B1 / A×100≤90, 50≤B2 / A×100, B2 / A×100-B1 / A×100≤60.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a disc brake pad for a disc brake of a car or truck, and more particularly to a disc brake pad having a friction material having a scorched friction surface. Background Art

[0002] Conventionally, a disc brake is used as a brake device for an automobile. The disc brake includes a disc brake pad as a friction member, in which a friction material is integrally bonded to a back plate.

[0003] The friction material of the disc brake pad is manufactured through the following steps: a mixing step of mixing a friction material composition including a binder, a fiber base material, a lubricating material, an organic friction adjusting material, an inorganic friction adjusting material, a pH adjusting material, and a filler to obtain a friction material raw material mixture; a heating and pressing molding step of overlapping the friction material raw material mixture and a backing plate and heating and pressing them with a thermoforming mold; and a heat treatment step of curing a thermosetting resin serving as a binder.

[0004] The disc brake pad is used in combination with a disc rotor made of cast iron as a counter-wear material, and generates braking force by pressing the friction material of the disc brake pad against both side surfaces of the rotating disc rotor.

[0005] Normally, when the brakes are used continuously, a phenomenon called thermal fading occurs in which the braking effectiveness decreases.

[0006] This thermal decay phenomenon occurs when the friction material of the disc brake pad is exposed to high temperature and high load. The organic matter contained in the friction material, such as the adhesive material or organic friction adjustment material, decomposes due to heat, producing gaseous or liquid decomposition products. The decomposition products between the friction material and the friction surface of the disc rotor act as lubricants, causing a decrease in braking efficiency.

[0007] In order to prevent thermal degradation of friction materials in the early stage of use, it is known that during the manufacturing process of friction materials, the friction surface of the friction material is subjected to high-temperature heating treatment such as hot plates, flames, lasers, etc., and a scorching treatment is performed to burn and remove organic matter that is the main factor causing thermal degradation.

[0008] Patent document 1 discloses a method for manufacturing a friction material, characterized in that a portion from the outer periphery of the friction material to the inner side that is shortest by 1 mm and longest by 10 mm is retained, and other portions are subjected to scorching treatment; and a method for manufacturing a friction material, characterized in that the entire surface of the friction material is subjected to scorching treatment, and then a portion from the outer periphery of the friction material to the inner side that is shortest by 1 mm and longest by 10 mm is retained, and other portions are subjected to re-scorching treatment.

[0009] According to the manufacturing method of Patent Document 1, by suppressing the decomposition of thermosetting resins, organic reinforcing fibers, etc. in the periphery of the friction material, it is possible to improve the braking performance during thermal decay without reducing the friction coefficient and wear resistance. However, there is a problem that sufficient braking performance cannot be obtained in normal use areas.

[0010] Patent Document 2 discloses a disc brake pad in which a friction material is brought into frictional contact with a disc rotor to generate a braking force, and the friction material is subjected to scorching treatment on at least one of both sides in the rotation direction of the disc rotor.

[0011] According to the disc brake pad of Patent Document 2, the occurrence of brake squealing can be suppressed by causing changes in physical properties such as reduced friction coefficient, reduced hardness, reduced strength, and improved hydrophobicity on at least one of the two sides of the friction material along the rotation direction of the disc rotor. However, since the central part of the friction surface of the friction material is not scorched, there is a problem that thermal decay cannot be effectively prevented.

[0012] On the other hand, cashew nut shell oil friction powder is used as an organic friction adjustment material in the friction material of disc brake pads. The role of cashew nut shell oil friction powder is to form a film on the friction surface of the disc rotor, generating adhesive friction, thereby exerting good and stable braking performance.

[0013] By scorching the friction surface of the friction material, organic matter such as cashew nut shell oil friction powder, which is the main factor causing the thermal decay phenomenon, is burned and removed, thereby effectively suppressing the thermal decay phenomenon of the disc brake pad in the early stage of use. However, when the cashew nut shell oil friction powder component on the friction surface of the friction material is burned and disappeared, a film of cashew nut shell oil friction powder is not formed on the friction surface of the disc rotor, resulting in a problem that sufficient braking performance cannot be obtained.

[0014] Prior art literature

[0015] Patent Literature

[0016] Patent Document 1: Japanese Patent Application Laid-Open No. 9-136971

[0017] Patent Document 2: Japanese Patent Application Laid-Open No. 10-318307 Summary of the invention

[0018] Problem that the invention aims to solve

[0019] The present invention is made in view of the above points and relates to a disc brake pad having a friction material for a disc brake of a car or truck, wherein the friction material has a scorched friction surface. The present invention aims to provide a disc brake pad that can prevent the disc brake pad from thermal degradation in the early stage of use and obtain sufficient braking performance.

[0020] Means used to solve problems

[0021] Conventional scorching treatment involves high temperature heating to make the thermal history of the friction surface of the friction material uniform and to make the scorched layer removed by burning organic matter have a uniform depth from the friction surface.

[0022] In this regard, it was found that by subjecting the friction surface to a scorching treatment, the thermal history received by the friction surface is partially different, so that the parts in the friction surface where organic matter such as cashew nut shell oil friction powder has been removed and the parts where more organic matter such as cashew nut shell oil friction powder remains exist at the same time, thereby preventing the thermal decay phenomenon in the early stage of use of the disc brake pad and obtaining sufficient braking performance, thereby completing the present invention.

[0023] The present invention relates to a disc brake pad having a friction material having a scorched friction surface for use in a disc brake of a car, truck or other vehicle, and is based on the following technology.

[0024] (1) A disc brake pad including a friction material having a friction surface that has been subjected to a thermal history by scorching, wherein the friction surface includes a mixture of a portion having a large thermal history by scorching and a portion having a relatively small thermal history by scorching.

[0025] (2) The disc brake pad according to (1), characterized in that when the mass reduction rate of the friction material interior that has not been subjected to the thermal history of scorching treatment when subjected to thermogravimetric analysis at 500°C is A, the mass reduction rate of the friction surface portion with the largest thermal history of scorching treatment when subjected to thermogravimetric analysis at 500°C is B1, and the mass reduction rate of the friction surface portion with a relatively small thermal history of scorching treatment relative to the portion with the largest thermal history of scorching treatment when subjected to thermogravimetric analysis at 500°C is B2, the following formula 1 is satisfied:

[0026] Formula 1: 30≤B1 / A×100≤90

[0027] 50≤B2 / A×100

[0028] B2 / A×100-B1 / A×100≤60.

[0029] (3) The disc brake pad according to (2), wherein the area ratio of the portion with the largest heat history of scorching treatment in the friction surface of the friction material is 10 to 90%.

[0030] The disc brake pad of the present invention performs scorching treatment on the friction surface of the friction material to remove part of organic matter such as cashew nut oil friction powder near the friction surface of the friction material, thereby effectively preventing the disc brake pad from thermal decay in the initial stage of use.

[0031] Furthermore, the friction material of the disc brake pad of the present invention has a friction surface having a mixture of a portion having a large thermal history of scorch treatment and a portion having a relatively small thermal history of scorch treatment relative to the portion having a large thermal history of scorch treatment.

[0032] Organic matter such as cashew nut shell oil friction powder is removed from the friction surface of the part with a large thermal history of the scorch treatment, while organic matter such as cashew nut shell oil friction powder remains relatively much on the friction surface of the part with a relatively small thermal history of the scorch treatment.

[0033] Therefore, a film of the cashew nut shell oil friction powder can be formed on the friction surface of the disc rotor, and due to the generated adhesive friction, good and stable braking performance can be obtained.

[0034] Effects of the Invention

[0035] According to the present invention, it is possible to provide a disc brake pad which can prevent the thermal degradation phenomenon in the early stage of use of the disc brake pad and obtain sufficient braking performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is an overall stereogram of the disc brake pad according to the present invention.

[0037] Figure 2 This is a flowchart showing an example of a method for manufacturing a disc brake pad.

[0038] Figure 3 is a cross-sectional view of a disc brake pad during a scorching process using a surface emitting laser module.

[0039] Figure 4 This is an explanatory diagram of a planar pattern of a scorched layer when the friction material is viewed from the friction surface side.

[0040] Figure 5 It is an enlarged partial cross-sectional view of a disc brake pad after the scorching treatment is completed. DETAILED DESCRIPTION

[0041] Edge Reference Figure 1 The disc brake pad according to the present invention will be described.

[0042] (1) Disc brake pads

[0043] The disc brake pad 10 includes a metal back plate 11 and a friction material 12 integrally bonded to one surface of the back plate 11 .

[0044] The present invention is constructed as follows: the thermal history received by the friction surface of the friction material through the scorching treatment is uneven, and there are a mixture of parts with a large thermal history of the scorching treatment and parts with a relatively small thermal history.

[0045] (2) Scorch treatment

[0046] In the manufacturing process described later, the friction material 12 is subjected to a scorching treatment so that the thermal history of the friction surface of the friction material 12 is partially different, including a portion (strongly treated portion) 13 having a large thermal history of the scorching treatment, and a portion (weakly treated portion) 14 having a relatively small thermal history of the scorching treatment relative to the portion 13 having a large thermal history of the scorching treatment.

[0047] In the area 13 of the friction surface where the heat history of the scorch treatment is large, organic matter such as cashew nut shell oil friction powder on the surface of the friction material is burned off, while in the area 14 where the heat history of the scorch treatment is relatively small compared to the area 13 of the friction surface where the heat history of the scorch treatment is large, organic matter such as cashew nut shell oil friction powder remains in a relatively large amount.

[0048] It should be noted that, in the present invention, the "region 14 having a relatively small thermal history of scorching" includes a case where the friction surface has no thermal history of scorching.

[0049] (3) The reason why the thermal history of the scorch treatment of the friction surface designed for the friction material is partially different from that of the structure.

[0050] In the present invention, the friction surface of the friction material 12 is designed to have a non-uniform thermal history of scorch treatment and a structure that has different parts.

[0051] With such a structure, a difference in the residual amount of organic matter such as cashew nut shell oil friction powder is set on the friction surface of the friction material 12. By utilizing the difference in the residual amount of organic matter such as cashew nut shell oil friction powder, the thermal decay phenomenon of the disc brake pad 10 in the early stage of use can be prevented, and sufficient braking performance can be obtained.

[0052] (3.1) Resistance to thermal decay

[0053] Since the friction surface of the friction material 12 is scorched and part of organic matter such as cashew nut oil friction powder existing near the friction surface is removed, the thermal degradation phenomenon of the disc brake pad 10 in the initial stage of use can be effectively prevented.

[0054] (3.2) Braking performance

[0055] The friction material 12 of the disc brake pad 10 of the present invention has a friction surface having a mixture of a portion 13 having a large thermal history of scorching treatment and a portion 14 having a relatively small thermal history of scorching treatment relative to the portion 13 having a large thermal history of scorching treatment.

[0056] Organic substances such as cashew nut shell oil friction powder remain relatively much on the friction surface of the area 14 having a relatively small thermal history of the scorching treatment compared to the area 13 having a large thermal history of the scorching treatment.

[0057] Therefore, when braking, a film of the cashew nut shell oil friction powder can be formed on the friction surface of the disc rotor, and due to the generated adhesive friction, good and stable braking performance can be obtained.

[0058] [Method for manufacturing disc brake pad]

[0059] Reference Figure 2 , Figure 3 A method for manufacturing a disc brake pad will be described.

[0060] (1) Mixing process

[0061] A friction material composition containing friction material raw materials such as a binder, a fiber base material, a lubricant, an organic friction modifier, an inorganic friction modifier, a pH modifier, and a filler is added to the The raw materials are stirred and mixed in a mixer such as a mixer or an Eirich mixer until they are uniformly dispersed to obtain a friction material raw material mixture.

[0062] (2) Preforming process

[0063] The friction material raw material mixture obtained in the mixing step is placed in a preforming mold and pressure-formed using a press device to obtain a preform of the friction material.

[0064] Before the preforming step, a kneading step of kneading the friction material raw material mixture using a pressure kneader to obtain a friction material raw material kneaded product or a granulating step of granulating the friction material raw material mixture to obtain friction material raw material granules may be provided.

[0065] (3) Heating and Pressing Molding Process

[0066] The preformed product obtained in the preforming process is overlapped with a steel back plate that has been pre-cleaned, surface-treated and coated with an adhesive and placed in a hot forming mold. A pressing device is used to perform heat and pressure molding for 1 to 10 minutes at a temperature of 140 to 200°C and a pressure of 20 to 80 MPa to obtain a molded product of the friction material.

[0067] It should be noted that the preforming step may be omitted and any one of the friction material raw material mixture, the friction material raw material kneaded product, and the friction material raw material granules may be placed in a hot forming mold and heated and pressurized to form the mixture.

[0068] (4) Grinding and other processing steps

[0069] The surface of the friction material is ground using a grinding device equipped with a grinding wheel to form a friction surface.

[0070] The surface of the friction material is chamfered or notched as required.

[0071] (5) Painting process

[0072] The parts of the disc brake pad other than the friction surface of the friction material are coated with paint by spray coating or electrostatic powder coating. The coating is baked at the same time as the following heat treatment process.

[0073] (6) Heat treatment process

[0074] The coated molded product is heated in a heat treatment furnace at 180-250°C for 1-5 hours to complete the curing reaction of the thermosetting resin contained in the friction material as a binder, and the paint applied in the coating process is baked at the same time.

[0075] (7) Scorch treatment process

[0076] Reference Figure 3 To explain, in the present invention, a vertical cavity surface emitting laser module 20 of a semiconductor laser (hereinafter referred to as "surface emitting laser module 20") is used as a heating method for scorching the friction material 12 formed on one surface of the back plate 11. By moving the surface emitting laser module 20 and the disc brake pad 10 relatively parallel to each other, and irradiating the friction surface of the friction material 12 with multiple lasers of different energy densities, a friction surface is formed in which a portion 13 with a large thermal history of scorching and a portion 14 with a relatively small thermal history of scorching compared to the portion 13 with a large thermal history of scorching are mixed.

[0077] The scorch treatment process will be described in detail below.

[0078] (7.1) Surface emitting laser module (VCSEL module)

[0079] The surface emitting laser module 20 is modularized by arranging a plurality of vertical cavity surface emitting laser (VCSEL) devices 21 (hereinafter referred to as "surface emitting laser devices 21") on a plane, and the laser energy density of each surface emitting laser device 21 can be varied.

[0080] The energy density of each surface emitting laser device 21 arranged relative to the surface of the friction material 12 is pre-set to the thermal history of the scorch treatment corresponding to the part of the friction surface of the friction material 12, so that it is easy to form a friction surface in which the part 13 with a large thermal history of the scorch treatment and the part 14 with a relatively small thermal history of the scorch treatment relative to the part 13 with a large thermal history of the scorch treatment are mixed.

[0081] As the surface emitting laser module 20, for example, a vertical cavity surface emitting laser module of Philipps Photonics manufactured by a method described in Japanese Patent Publication No. 2015-510279 can be used. The surface emitting laser device 21 is not limited to a vertical cavity surface emitting laser.

[0082] (7.2) Energy density

[0083] The energy density of the area 13 with a large thermal history of scorching treatment is 150 to 1100 kW / m 2 The energy density of the area 14 with a relatively small thermal history of the scorch treatment is 0 to 300 kW / m 2 .

[0084] (7.3) Irradiation distance

[0085] When the friction material 12 is subjected to the scorching treatment, the distance (irradiation distance) G between the irradiation surface of the surface emitting laser device 21 and the surface of the friction material 12 is 15 to 300 mm, preferably 30 to 200 mm, and more preferably 50 to 100 mm.

[0086] (7.4) Processing time

[0087] The time for scorching the friction material 12 is 0.5 to 60 seconds, preferably 3 to 10 seconds, and more preferably 4 to 8 seconds.

[0088] If the scorching treatment time exceeds 60 seconds, a large amount of organic matter on the surface of the friction material will be burned and the strength will be significantly reduced.

[0089] (7.5) Configuration of surface emitting lasers

[0090] The arrangement of the surface emitting laser module 20 relative to the friction material 12 is not limited to the following. Figure 3 The surface emitting laser modules 20 may be arranged in parallel with the disc brake pad 10 , or may be arranged in a longitudinal direction along the friction material 12 , or may be arranged in a splayed manner around the friction material 12 .

[0091] (7.6) Planar pattern (planar shape) of the scorched layer

[0092] By parallel moving either or both of the surface emitting laser module 20 or the disc brake pad 10, a friction surface can be formed in which a portion 13 with a large thermal history of scorch treatment and a portion 14 with a relatively small thermal history of scorch treatment are mixed.

[0093] When the friction material 12 is viewed from the friction surface side, the plane pattern formed by the portion 13 with a large thermal history of scorching treatment is not limited to Figure 1 The stripe pattern shown along the longitudinal direction of the friction material 12 can also form, for example Figure 4 The stripe pattern ( Figure 4 (a)), oblique stripe pattern ( Figure 4 (b)), lattice pattern ( Figure 4 (c)), ripple pattern ( Figure 4 (d)), any one of the houndstooth patterns (not shown), or a combination of multiple ones.

[0094] The planar shape of the portion 13 with a large thermal history of scorching treatment alone is not limited to a straight line, but may be a curved line.

[0095] The planar shape of the portion 13 with a large thermal history of scorching treatment alone is not limited to a continuous band-like surface, but may be formed intermittently like a dotted line or in a dotted shape like a water drop pattern.

[0096] The width dimension and formation interval of the portion 13 having a large thermal history of scorching treatment can be appropriately selected.

[0097] As described above, in the present invention, the surface emitting laser module 20 and the disc brake pad 10 are relatively moved, and multiple lasers with different energy densities are irradiated onto the friction surface of the friction material 12, so that the disc brake pad 10 having the friction material 12 with partially different thermal history of scorch treatment can be easily manufactured.

[0098] [Method for determining the size of thermal history]

[0099] Reference Figure 5A method for determining the thermal history of the friction material 12 subjected to the scorch treatment will be described.

[0100] In the present invention, thermogravimetric analysis (TGA) is used as a method for determining the thermal history of the friction material 12 subjected to the scorch treatment.

[0101] (1) Principles of thermal history judgment

[0102] The magnitude of the thermal history of the friction material 12 caused by the scorching treatment can be determined by the mass reduction rate of a surface sample collected from the surface of the friction material 12 that has undergone the thermal history of the scorching treatment and an internal sample collected from the inside of the friction material 12 that has not undergone the thermal history of the scorching treatment during thermogravimetric analysis.

[0103] (1.1) Method for collecting samples from the friction material surface

[0104] The surfaces of the friction material 12 at two locations, a site 13 having a large thermal history of scorching treatment and a site 14 having a relatively small thermal history of scorching treatment relative to the site 13 having a large thermal history of scorching treatment, were scraped to a depth of 0.1 mm using a drill with a 6 mm diameter drill bit, and 20 mg of surface samples were collected from each location.

[0105] (1.2) Method for collecting samples inside friction materials

[0106] Using a grinder, the surface of the scorched friction material 12 was ground to a depth of 3 mm from a position where the surface had no thermal history of the scorching treatment.

[0107] Then, the surface of the ground friction material 12 was scraped to a depth of 0.1 mm using a drill with a drill bit having a diameter of 6 mm, and a 20 mg internal sample was collected.

[0108] (1.3) Definition of mass reduction rate

[0109] When the samples (surface sample and internal sample) collected from the friction material 12 are subjected to thermogravimetric analysis, the mass reduction rate of each sample is defined as follows.

[0110]

[0111] The mass reduction rate when thermogravimetric analysis was performed on each sample collected from the friction material 12 was as follows.

[0112] In the friction material 12 that has not undergone the thermal history of scorching treatment, organic matter such as cashew nut shell oil friction powder has not been removed, so the mass reduction rate A in the thermogravimetric analysis is the largest.

[0113] In the area 13 of the friction surface 12 where the thermal history of the scorching treatment is the largest, organic matter such as cashew nut shell oil friction powder is removed the most, so the mass reduction rate B1 in the thermogravimetric analysis of the surface of the friction material 12 is the smallest.

[0114] Compared with the area 13 of the friction surface 12 having the largest thermal history of scorching treatment, the area 14 having a relatively small thermal history of scorching treatment has a relatively small amount of organic matter such as cashew nut shell oil friction powder removed, so the mass reduction rate B2 during the thermogravimetric analysis of the friction material surface is greater than the above-mentioned mass reduction rate B1.

[0115] It should be noted that when the portion 14 with a relatively small thermal history of scorching treatment has no thermal history of scorching treatment, the mass reduction rate B2 of the surface of the friction material 12 in thermogravimetric analysis is substantially the same as the mass reduction rate A inside the friction material 12.

[0116] As can be seen from the above, the relationship of the mass reduction rate when the friction material surface is subjected to thermogravimetric analysis at 500° C. satisfies A≥B2>B1.

[0117] (1.4) Relationship of mass reduction rate

[0118] Regarding the magnitude of the thermal history of the scorch treatment of the friction material 12, the mass reduction rate measured by thermogravimetric analysis using a surface sample of the friction material 12 and an internal sample of the friction material 12 that has not undergone the thermal history of the scorch treatment satisfies the following equation.

[0119] By satisfying the following equation, it is possible to prevent the disc brake pad 10 from thermally fading in the initial period of use while obtaining sufficient braking performance.

[0120] If the following formula is not satisfied, the above-mentioned effect cannot be obtained, and in addition, problems such as deterioration of wear resistance and deterioration of flatness of the friction surface may occur.

[0121] Formula 1: 30≤B1 / A×100≤90·············(a)

[0122] 50≤B2 / A×100················(b)

[0123] B2 / A×100-B1 / A×100≤60···(c).

[0124] (2) Area ratio of the part with the largest thermal history of scorch treatment

[0125] The present invention satisfies the above-mentioned formula 1 and satisfies that the area ratio of the portion 13 having the largest thermal history of scorch treatment in the friction surface of the friction material 12 is within a range of 10 to 90%.

[0126] The area ratio of the portion 13 having the largest thermal history of the scorching treatment is preferably 30 to 70%, more preferably 40 to 60%.

[0127] By setting the area ratio of the portion 13 with the largest thermal history of the scorching treatment within the above range, the performance of the thermal fade resistance and the braking performance can be further improved.

[0128] (3) Thermogravimetric analysis

[0129] Thermogravimetric analysis was performed using a differential thermal analyzer (Thermo plus EVO TG8120 manufactured by Rigaku Corporation) under the following conditions. The thermogravimetric reduction rate was calculated from the weight reduction amount from room temperature to 500°C.

[0130] environment Air Sample 10mg Standard specimen α-Alumina Measuring temperature Room temperature~800℃ Heating rate 20℃ / min

[0131] Example

[0132] The present invention will be specifically described below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples.

[0133] 1. Methods of manufacturing disc brake pads of Examples 1 to 26 and Comparative Examples 1 to 9

[0134] The friction material composition having the composition shown in Table 1 was used The mixture was mixed in a mixer for 5 minutes and pre-molded by applying pressure at 30 MPa for 10 seconds in a molding die.

[0135] The preformed product is stacked on a steel back plate that has been cleaned, surface-treated, and coated with an adhesive material in advance, and is formed in a hot forming mold at a forming temperature of 150°C and a forming pressure of 40 MPa for 10 minutes. It is then coated with electrostatic powder and subjected to a heat treatment (post-curing) at 200°C for 5 hours, which also serves as paint baking, and then ground to form a friction surface.

[0136] [Table 1]

[0137]

[0138] Next, a scorching treatment was performed under the conditions shown in Tables 2 and 3 to produce disc brake pads (Examples 1 to 26 and Comparative Examples 1 to 9).

[0139]

[0140]

[0141] 2. Evaluation Criteria

[0142] The obtained disc brake pads were evaluated for thermal fade resistance, braking performance, wear resistance, and flatness.

[0143] <1>Resistance to thermal decay

[0144] According to JASO C406 "Passenger car - Braking system - Bench test method", the minimum friction coefficient μ in the first thermal decay test was measured. The evaluation criteria are as follows.

[0145] evaluate Minimum friction coefficient μ excellent 0.30 and above good 0.25 or more and less than 0.30 qualified 0.20 or more and less than 0.25 Failure Less than 0.20

[0146] <2>Braking performance

[0147] The average friction coefficient μ in the second effectiveness test was measured according to JASO C406 "Passenger car-Braking device-Bench test method". The evaluation criteria are as follows.

[0148] evaluate Average friction coefficient μ excellent 0.45 and above good 0.42 or more and less than 0.45 qualified 0.38 or more and less than 0.42 Failure Less than 0.38

[0149] <3>Abrasion resistance

[0150] According to JASO C427 "Automobile - Brake lining and disc brake pad - Bench wear test method", the wear amount (mm) of the friction material is measured under the conditions of initial braking speed of 50km / h, braking deceleration of 0.3G, appropriate number of braking times, and brake temperature of 200℃ before braking, and converted into the wear amount per 1000 braking times.

[0151] The evaluation criteria are as follows.

[0152] evaluate Wear amount of friction material (mm) excellent Less than 0.15mm good 0.15mm or more and less than 0.20mm qualified 0.20mm or more and less than 0.50mm Failure 0.50mm or more

[0153] <4>Flatness of friction surface

[0154] Place three support blocks on the flat plate to make the height uniform, support three points on the end of the back plate with the support blocks, and use a micrometer to measure the height of the five locations with the largest thermal history of scorch treatment on the friction surface and the height of the five locations with relatively small thermal history of scorch treatment relative to the location with the largest thermal history of scorch treatment on the friction surface. Calculate the difference between the highest and lowest parts in height. The evaluation criteria are as follows.

[0155] evaluate Flatness of friction material (μm) excellent Less than 70μm good 70μm or more and less than 100μm qualified 100μm or more and less than 150μm Failure 150μm

[0156] 3. Evaluation results

[0157] The evaluation results are shown in Tables 4 and 5.

[0158]

[0159] It can be seen from the above table that the friction material 12 that meets the conditions of the present invention is good in various evaluation items such as thermal decay resistance, braking performance, wear resistance, and flatness.

[0160] Industrial Applicability

[0161] According to the present invention, a disc brake pad is provided, which is a disc brake pad with a friction material. The friction material has a friction surface that has been scorched, which can prevent the disc brake pad from thermal degradation in the early stage of use, while obtaining sufficient wear resistance and braking efficiency, and has extremely high practical value.

[0162] Explanation of symbols

[0163] 10 Disc brake pads

[0164] 11 Back Panel

[0165] 12 Friction material

[0166] 13 The area with the largest thermal history of scorch treatment

[0167] 14 The area with the largest thermal history of scorch treatment is relatively small compared to the area with the largest thermal history of scorch treatment.

[0168] 20 Surface Emitting Laser Modules

[0169] 21 Surface emitting laser devices.

Claims

1. A disc brake pad comprising a friction material having a friction surface subjected to a thermal history by a scorching treatment, It is characterized in that The scorching treatment is performed by using a surface emitting laser module, while moving one or both of the surface emitting laser module and the disc brake pad in parallel, irradiating the friction surface of the friction material with an energy density of 150 to 1100 kW / m 2 and 0~300kW / m 2 And multiple lasers with different energy densities, The friction surface contains a mixture of areas with a large thermal history of scorch treatment and relatively small areas. When the friction material that has not been subjected to the thermal history of scorch treatment is subjected to thermogravimetric analysis at 500°C, the mass reduction rate is A. The mass reduction rate of the friction surface at the site with the largest thermal history of scorch treatment when subjected to thermogravimetric analysis at 500°C is B1. When the mass reduction rate of the site with the largest thermal history of scorch treatment relative to the site with the largest thermal history of scorch treatment on the friction surface during thermogravimetric analysis at 500° C. is B2, the following formula 1 is satisfied: Formula 1: 30≤B1 / A×100≤90 50≤B2 / A×100 B2 / A×100-B1 / A×100≤60.

2. The disc brake pad according to claim 1, characterized in that In the friction surface of the friction material, the area ratio of the portion with the largest thermal history of scorching treatment is 10 to 90%.